PERCEPTION OF BUSINESS EDUCATION STUDENTS ON SMALL AND MEDIUM SCALE ENTERPRISES AS A TOOL FOR REDUCING GRADUATES’ UNEMPLOYMENT - Egbri, Jane Nwakego; Owenvbiugie, Robinson Osarumwense (Sokoto Educational Review, 2021)
The study assessed the homegrown school feeding programme for the prevention of dropout of pupils in public primary schools in Delta State. Two research questions were raised to guide the study and a null hypothesis was tested at 0.05 level of significance for the study. The study utilized a descriptive survey research design. The population of the study was 571 teachers in 55 primary schools in Ika South Local Government Area of Delta State in the 2020/2021 academic session. A proportionate sampling technique was used to randomly select 200 teachers. Three experts validated the instrument and Cronbach alpha statistics tested reliability and yielded a correlation coefficient of 0.71. Data was collected using a questionnaire. Descriptive statistics of mean and standard deviation were used to answer the research questions. The t-test was used to test the hypothesis. From the results of the analysis, it was concluded that home grown school feeding programme has a high influence on the prevention of pupils' dropout rate and increasing regular attendance in public primary schools in Delta State. Experienced and less experienced teachers did not differ significantly in their rating on the influence of homegrown school feeding programmes on primary school pupils' dropout rate in Delta State hence the null hypothesis was accepted. Consequently, it was recommended that the Government and other stakeholders in charge of the programme should remain committed to providing the needed resources for the smooth running of the programme to improve the educational fortune of the beneficiaries. Furthermore, policy makers and implementers should embark on a careful examination of the programme by involving local communities instead of depending on donors to ensure the sustainability of the programme.